Impact of Low Maternal Education on Early Childhood Overweight and Obesity in Europe. Issue 3 (4th March 2016) - Ruiz, Milagros; Goldblatt, Peter; Morrison, Joana; Porta, Daniela; Forastiere, Francesco; Hryhorczuk, Daniel; Antipkin, Youriy; Saurel‐Cubizolles, Marie‐Josèphe; Lioret, Sandrine; Vrijheid, Martine; Torrent, Maties; Iñiguez, Carmen; et al.
Abstract: Background: Comparable evidence on adiposity inequalities in early life is lacking across a range of European countries. This study investigates whether low maternal education is associated with overweight and obesity risk in children from distinct European settings during early childhood. Methods: Prospective data of 45 413 children from 11 European cohorts were used. Children's height and weight obtained at ages 4–7 years were used to assess prevalent overweight and obesity according to the International Obesity Task Force definition. The Relative/Slope Indices of Inequality (RII/SII) were estimated within each cohort and by gender to investigate adiposity risk among children born to mothers with low education as compared to counterparts born to mothers with high education. Individual‐data meta‐analyses were conducted to obtain aggregate estimates and to assess heterogeneity between cohorts. Results: Low maternal education yielded a substantial risk of early childhood adiposity across 11 European countries. Low maternal education yielded a mean risk ratio of 1.58 (95% confidence interval (CI) 1.34, 1.85) and a mean risk difference of 7.78% (5.34, 10.22) in early childhood overweight, respectively, measured by the RII and SII. Early childhood obesity risk by low maternal education was as substantial for all cohorts combined (RII = 2.61 (2.10, 3.23)) and (SII = 4.01% (3.14, 4.88)). Inequalities in early childhood adiposity were consistent among boys, but varied among girls in a few cohorts. Conclusions: Considerable inequalities in overweight and obesity are evident among European children in early life. Tackling early childhood adiposity is necessary to promote children's immediate health and well‐being and throughout the life course.